Systemic biomarkers of eosinophilic chronic rhinosinusitis. Issue 1 (February 2020) - Ho, Jacqueline; Earls, Peter; Harvey, Richard J.
Abstract : Purpose of review: The current understanding of eosinophilic chronic rhinosinusitis (CRS) has developed rapidly over the past decades. Classification of CRS based on the inflammatory endotype more accurately reflects the underlying pathophysiology and better directs treatment. Corticosteroids and more recently biologic agents, target the eosinophil inflammatory that drives this subtype of CRS. Tissue sampling is not always accessible or available and surrogate markers are sought to define this endotype of CRS. The purpose of this review is to assess current systemic predictors of eosinophilic CRS (eCRS) diagnosis. Recent findings: Blood eosinophils are a moderate surrogate predictor of eCRS. A blood eosinophil count of more than 0.24 × 10 9 /l predicts eCRS with tissue eosinophilia of more than 10 eosinophils per high-power field. It has been further shown that a blood eosinophil count more than 0.45 × 10 9 /l is associated with need for long-term systemic therapy following endoscopic sinus surgery. Other biomarkers reviewed include IgE, eosinophilic cationic protein, eosinophil-derived neurotoxin, eosinophil peroxidase, IL-5, periostin, eotaxin-3 and IL-16. Summary: There remains limited data surrounding the prognostic use of biomarkers in eCRS. However, peripheral eosinophilia best predicts the eosinophilic density that best predicts the eCRS phenotype. In addition, it is also prognostic of need for more intensive therapy. Simple haematoxylin and eosin stained sinus mucosa still remains the most reliable tissue for assessment and is more accessible than bronchial biopsies